2015
DOI: 10.12816/0025396
|View full text |Cite
|
Sign up to set email alerts
|

Physicohemical Properties of Doum (Hyphaene thebaica) Fruits and Utilization of its Flour in Formulating Some Functional Foods

Abstract: Doum (Hyphaene thebaica) fruit, and doum-fruit flour (DFF) were studied in terms of physicohemical properties as well as technological processing to prepare biscuits, crackers and pudding containing DFF. Chemical composition showed that DFF possessed low contents of crude protein and crude ether extract being, 2.87 and 0.76%, respectively. Non reducing sugars represented about (91.94 %) of the total sugars (43.70%). The DFF could be considered as a good source of minerals (K, Ca, Na, and Mg). The results also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Kulit buah zuriat bisa dimakan dan ditumbuk menjadi bubuk atau dipotong menjadi irisan. Selain itu, bubuk kulit buah zuriat juga dapat dikeringkan kemudian ditambahkan ke makanan sebagai penyedap rasa (Aamer, 2015). Selain sebagai bahan makanan, buah zuriat juga berkhasiat untuk kesehatan.…”
Section: Aspek Formatunclassified
See 1 more Smart Citation
“…Kulit buah zuriat bisa dimakan dan ditumbuk menjadi bubuk atau dipotong menjadi irisan. Selain itu, bubuk kulit buah zuriat juga dapat dikeringkan kemudian ditambahkan ke makanan sebagai penyedap rasa (Aamer, 2015). Selain sebagai bahan makanan, buah zuriat juga berkhasiat untuk kesehatan.…”
Section: Aspek Formatunclassified
“…Buahnya berwarna coklat sampai kemerahan, halus, tidak berbulu, cekung atau berbintik-bintik dan daging buahnya mengandung zat manis yang kuat (Fanshawe, 1966). Buah zuriat dikenal sebagai buah liar yang bisa dimakan dan dikonsumsi (Aamer, 2015). Buah zuriat merupakan salah satu buah kaya akan antioksidan, dan telah dimanfaatkan dalam pengobatan diabetes, obesitas, hipertensi, dislipidemia, dan untuk meringankan penyakit kardiovaskular (Kolla, dkk., 2021).…”
unclassified
“…Although the leafy stem is used for construction, the foliage is used to make hats, mats, ropes, and baskets [11]. The doum palm is used to treat bilharziasis and its fruit is sometimes chewed to decrease high blood pressure [12,13]. [14] reported that the doum palm fruit pulp's proximate composition included the following: protein (2.86%), fat (0.92%), ash (6.24%), crude fiber (12.87%), moisture (8.64%), and carbohydrates (68.47%).…”
Section: Introductionmentioning
confidence: 99%
“…Doum fruit (Hyphaene thebaica L.), belonging to the family of Arecaceae [16], is widespread in the Sahel and tends to grow in areas where groundwater is present and is found along the Nile River in Egypt, Sudan [17] and Western India [16]. Doum fruit is registered as one of the most beneficial and useful plants in the world [18]. It has a taste like gingerbread and has an oblong, yellow-orange apple sized fruit with red outer skin, a thick, spongy and rather sweet and fibrous fruit pulp [19].…”
Section: Introductionmentioning
confidence: 99%